PENGARUH MODEL DISCOVERY LEARNING DENGAN METODE LATERAL THINKING TERHADAP KEMAMPUAN BERTANYA SISWA KELAS X IPA SMAN 2 KARANGANYAR - Aurlena, Weny Puput; Sudarisman, Suciati; Ariyanto, Joko (Universitas Sebelas Maret, 2016)
This research aimed to find out the effect of discovery learning with lateral thinking on questioning ability of the 10th IPA graders of SMAN 2 Karanganyar.This study was a quasi experimental research with post-test only with non-equivalent group research design. The population of research was all of the 10th graders of SMAN 2 Karanganyar. The sampling technique used was cluster sampling one. The 10th IPA 2 grade served as experiment group and the 10th IPA 3 as control. Techniques of collecting data used were test and non-test. Test technique employed essay question instrument to measure the learning outcome in cognitive domain, while non-test technique used observation sheet instrument to measure the students’ questioning ability, learning outcome in psychomotor and affective domains and the implementation of learning syntax. Hypothesis testing was carried out using t-test with SPSS version 17 help.The results showed that the ability to ask students between the experimental group and the control group were significantly different . Values experimental group students' ability to ask include: questions asking for an explanation of 1.54 ; The question of what , why and how 36.18 ; background hypothetical question 40.13 . Value KPS control groups included: the question asked for an explanation of 0.57 ; The question of what , why and how 41.03 ; background hypothetical question 29.06 This research concluded that there was an effect of discovery learning model with lateral thinking method on the questioning ability of the 10th IPA graders of SMAN 2 Karanganyar. Keywords: discovery learning, lateral thinking, questioning ability